Le public chez Dewey : une union sociale plurielle - Joëlle Zask (Tracés, 2008)
Citizenship is a problematic institution. Over history, citizens have been hauled between two contradictory requirements: to participate or to gain the required competence to judge fairly on public affairs. The central argument of this paper is that only an agreement based on plurality can lead to an enduring coordination between these two requirements. John Dewey’s social and political philosophy provides us with the basis for such a combination between taking part and developing an actual public opinion: the “public” is presented as an agency organized internally as a community of investigators. In order to shed light on the original character of this conception, the “public” is contrasted with other formations based on identity, such as the “mass” or “people”.